ANALYSIS OF THE RELATIONSHIP BETWEEN COMPLIANCE AND SUCCESSFUL THERAPY FOR PROLANIS - HYPERTENSION PATIENTS AT 2 COMMUNITY HEALTH CENTERS IN BANDUNG CITY THROUGH MEDICATION CARD PROVISION - Sarah
Compliance is one of the determinants of successful therapy for hypertensive patients with complex treatment regimens. Medication reminder cards can be used as tools to improve compliance. This study aims to analyze the influence of medication reminder card on compliance and the correlation between compliance and the success of hypertension therapy in two primary healthcare centers in Bandung City. Patient compliance level was assessed using the validated 8-item Morisky Medication Adherence Scale (MMAS-8), and the therapy success followed the Joint National Committee 8 Hypertension Guideline Algorithm (JNC 8). The study design used observational with a crosssectional study design. Data collection was done retrospectively and concurrently from January to May 2023. The results of the study showed that the distribution of medication reminder cards had a significant influence on increasing patient compliance (p<0.05). In Pasundan Health Center 18 hypertensive patient (66.6%) and 14 hypertensive with diabetes patients (66.6%) experienced improved compliance after receiving cards. In Ibrahim Adjie Health Center, 7 hypertensive patients (77.78%) and 6 hypertensive and diabetes patients (54.54%) also showed increased compliance after receiving medication reminder cards. Through correlation analysis between compliance and therapy success data, weak correlation were found with values of (r = -0.085) for hypertension in Pasundan Health Care, (r = 0.080) for hypertension with diabetes in Pasundan Health Care, (r = -0.223) for hypertension in Ibrahim Adjie Health Care, and (r = 0.245) for hypertension with diabetes in Ibrahim Adjie Health Care.